Indonesian optimal sarcopenia cutoff values of calf circumference, muscle strength, and physical performance: a multicenter descriptive and cross-sectional study - Setiati, Siti; Kamaruzzaman, Shahrul Bahyah; Chew, Samuel Teong Huang; Kemala Sari, Nina; Harimurti, Kuntjoro; Laksmi, Purwita Wijaya; Aryana, I Gusti Putu Suka; Sunarti, Sri; Dwimartutie, Noto; Fitriana, Ika; Asylia Dinakrisma, Anastasia; Azwar, Muhammad Khifzhon; et al. (Frontiers in Medicine, 2025)
IntroductionThe prevalence of possible sarcopenia among Indonesian older adults using the Asian Working Group for Sarcopenia (AWGS) 2019 consensus cutoffs was abnormally high compared with reported prevalence in other East Asian countries. This suggests that the current AWGS cutoff values may not be applicable to the Indonesian population as it did not contain reference statistical values based on the local population normative studies. This lack of local data may result in inaccurate assessments and diagnoses of sarcopenia among Indonesian population. We therefore aimed to conduct a nationwide study in the community to obtain optimal cutoff values for calf circumference, muscle strength, and physical performance for the diagnosis of sarcopenia in Indonesia.MethodsIn this multicenter descriptive and cross-sectional study, we collected data from healthy adults aged 20–39 years in different islands in Indonesia. We followed the recommendation by the European Working Group for Sarcopenia in Older People (EWGSOP) of using 2 standard deviations [SD] below the mean of a young healthy cohort for the new cutoff points of sex-specific handgrip strength, calf circumference, and gait speed. The mean +2 SD was used for five times sit-to-stand test (FTSTST).ResultsThe mean −2 SD value of male handgrip strength was 21.15 kg, and 14.34 kg for female subjects. The mean −2 SD value of male and female calf circumferences were 29.92 cm, and 26.70 cm, respectively. Two SD below the mean of gait speed results was 0.51 s, whereas 2 SD above mean of FTSTST results was 11.69 s.DiscussionThe suggested cutoff values for low calf circumference, muscle strength, and gait speed in Indonesian population are different from those in previous consensuses. Body morphology, culture, and obesity may be the factors related to this phenomenon. This study contributes to the body of literature of normative data used to determine cutoff values used in the diagnosis of sarcopenia in Indonesian and Asian populations.